Kepemimpinan Pendidikan dalam Pembinaan SDM - Istikhori Istikhori; Doa Fajarwati; Nurasiah Jamil; Yeni Yulianti; Alfian Khadafi (Lembag, 2025)
Leaders are the decisive factors in the success or failure of an organization and effort. Whether in the business or in education, health, company, relegi, social, political, state government, and so forth, a leader's quality determines the success of an institution or organization. Leadership is an unavoidable social fact of arranging relationships between individuals associated with one society. Where each individual has a collective purpose that wants to be realized together in society. On this research will be concerned about how leadership education in human resources. As for the research methods used in this study are qualitative research methods, to be exact library research. With a documentary data collection technique and data analysis analysis of content analysis. The results of this study show that the ideal nature of leaders in Islam is knowledge, the spirit of calling upon goodness, noble virtue, istiqomah, patience, justice, honesty, discipline, the soul responsible and has the spirit to build. Leaders must inspire and instill a spirit of cooperation in realizing Shared vision and mission.